Perspective: Of Mice and Men – How Widespread Is Adult Neurogenesis? - Petrik, David; Encinas, Juan M. (Frontiers in Neuroscience, 2019)
These are exciting times for research on adult hippocampal neurogenesis (AHN). Debate and controversy regarding the existence of generation of new neurons in the adult, and even diseased human brain flourishes as articles against and in favor accumulate. Adult neurogenesis in the human brain is a phenomenon that does not share the qualities of quantum mechanics. The scientific community should agree that human AHN exists or does not, but not both at the same time. In this commentary, we discuss the latest research articles about hAHN and what their findings imply for the neurogenesis field.